Adsorption of anionic dyes on Fe(III)-loaded collagen fibre from aqueous solution. (17th October 2008) - Gu, Ying-Chun; Liao, Xue-Pin; Huang, Yan-Jie; Shi, Bi
A novel adsorbent, Fe(III)-loaded collagen fibre (FLCF), was prepared and its adsorption behaviours to three kinds of anionic dyes, Direct Yellow 11 (DY11), Acid Yellow 11 (AY11) and Reactive Blue 19 (RB19), were investigated. It was found that the highest adsorption capacity appeared at pH 3 and that the effect of temperature was not remarkable on the adsorption of AY11 and RB19, whilst considerable on the adsorption of DY11. The maximum adsorption capacities at 313 K were found to be 431.0 mg g−1, 485.2 mg g−1 and 311.8 mg g−1 for DY11, AY11 and RB19, respectively, and the adsorption equilibrium data could be well fitted by the Langmuir model. Furthermore, the adsorption kinetics could be well described by the pseudo-second-order rate model, and the adsorption capacities calculated by this model were close to the values actually determined, which implied that chemical reaction should be the rate-controlling step.